2009
DOI: 10.2319/012208-37.1
|View full text |Cite
|
Sign up to set email alerts
|

Water and Saliva Contamination Effect on Shear Bond Strength of Brackets Bonded with a Moisture-Tolerant Light Cure System

Abstract: Objective: To evaluate the effects of water and saliva contamination on shear bond strength of brackets bonded with a moisture-tolerant light cure system. Materials and Methods: Brackets were bonded to 240 bovine lower incisors divided into 12 groups. Four bonding procedures were evaluated, including (1) TSEP/Transbond XT, (2) TMIP/ Transbond XT, (3) TSEP/Transbond PLUS, and (4) TMIP/Transbond PLUS, each under three different bonding conditions: without contamination, with water contamination, and with saliva … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
2
22
1
Order By: Relevance
“…Findings of this study are quite comparable to the study done by Vicente et al .,[12] on SEP and MIPs. They concluded that under contaminated condition, SEP and MIP primer should be used in conjunction with hydrophilic adhesive system rather than hydrophobic system.…”
Section: Discussionsupporting
confidence: 92%
“…Findings of this study are quite comparable to the study done by Vicente et al .,[12] on SEP and MIPs. They concluded that under contaminated condition, SEP and MIP primer should be used in conjunction with hydrophilic adhesive system rather than hydrophobic system.…”
Section: Discussionsupporting
confidence: 92%
“…Although the self-etching adhesive contained less than 2% in weight of bisphenol A diglycidyl ether dimethacrylate (bis-GMA), it included polyethylene glycol dimethacrylate (PEGDMA) in its composition, which might have enhanced its tolerance of wet conditions. [25]…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Few studies are available showing reduced bracket shear bond strength on fluorosed enamel. [18][19][20] However, no literature has been found on bracket bond strength with demineralized dental hard tissue.…”
Section: Introductionmentioning
confidence: 99%